2018
DOI: 10.7326/m18-2261
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Risk Factors for Chronic Opioid Use Among Opioid-Naive Patients With Newly Diagnosed Musculoskeletal Pain in the Neck, Shoulder, Knee, or Low Back

Abstract: Background. Musculoskeletal pain is a common condition, raising the concern these patients may transition to chronic opioid use. However, the incidence of and risk factors for chronic opioid use among patients with new musculoskeletal pain are not fully understood. Objective. To characterize the incidence and risk factors of chronic opioid use among opioid-naive patients with newly diagnosed musculoskeletal pain in the knee, neck, low back, and/or shoulder. Methods and Findings. The IBM® Marketscan® databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 3 publications
1
19
1
Order By: Relevance
“…However, the prevalence of opioid use and opioid use disorder among this construction cohort is much higher than other populations. Moshfegh and George 44 found that the risk of developing long‐term opioid use among opioid‐naïve patients with new musculoskeletal disorders was less than 1%,—far below the 6.3% risk we found among construction workers diagnosed with chronic musculoskeletal disorder and the 2.4% risk among the workers with acute musculoskeletal injuries. Another study 34 showed that 12% of construction workers received chronic prescriptions, suggesting workers seek treatment for ongoing pain.…”
Section: Discussioncontrasting
confidence: 57%
“…However, the prevalence of opioid use and opioid use disorder among this construction cohort is much higher than other populations. Moshfegh and George 44 found that the risk of developing long‐term opioid use among opioid‐naïve patients with new musculoskeletal disorders was less than 1%,—far below the 6.3% risk we found among construction workers diagnosed with chronic musculoskeletal disorder and the 2.4% risk among the workers with acute musculoskeletal injuries. Another study 34 showed that 12% of construction workers received chronic prescriptions, suggesting workers seek treatment for ongoing pain.…”
Section: Discussioncontrasting
confidence: 57%
“…However, the extent of this decrease was not significant among patients with neck pain [29]. Machado et al pointed out that there have been very few trials aimed at showing the effectiveness of NSAIDs on neck pain [30].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies showed that there was a significant decrease in opioid use by patients with low back, neck, knee, and shoulder pain between 2008 and 2014 in the USA [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 38 People with newly diagnosed MSK pain who were opioid-naive when seeking care and subsequently received an opioid prescription had increased risk of chronic opioid use (defined as ≥10 prescriptions or ≥120 days supply between 91 and 365 days after the initial diagnosis). 35 The risk of transitioning from opioid-naive to chronic opioid use for newly diagnosed MSK pain was highest for people with low back pain or with multiple areas of pain (eg, knee and low back pain). 35 Reliance on opioid medication for MSK pain management has led to calls for a shift to providing care models that support nonpharmacologic therapies.…”
Section: Introductionmentioning
confidence: 99%